Experimental analysis of Thermal Efficiency of functionalized Graphene (COOH) reinforced PCM for thermal energy storage system. Issue 1 (April 2021) - Singh, Pradeep Kumar; Nagar, Sumit; Singh, Mahendra
Abstract: In this work, the emphasis is on the thermal conductivity of paraffin wax and nano material which is functionalized graphene (COOH). Firstly COOH graphene is combined in various concentrations with paraffin wax to achieve higher thermal conductivity and then it is analysed for thermal conductivity having flow rate of heat transfer fluid(HTF) as 50ml at 8 second. When COOH functionalized graphene is used in this experiment, the thermal conductivity of paraffin wax increases. This study included experiments on varying concentrations of functionalized graphene (COOH) and inlet HTF temperatures for thermal properties, density, specific heat and nanofluid properties. The graphene is combined by stirring it with the paraffin wax. Graphene concentrations are 0.25 volume%, 0.5 volume% and 0.75 volume% for the flow rate of 50 ml in 8 second. Thermal conductivity increases with increase in the concentration of graphene. In the winter season, where environmental losses are higher than the summer season and the air temperature is 18°C, while it is above 29°C in the summer season, it also reduces PCM charging time around 30 to 50 percent with the use of functionalized graphene. In all concentrations, HTF temperature varies from 80°C to 90°C, with observed input energy, environmental losses, charging time, charging rate and performance. All values are noted after a 10 minute interval, till the cylinder is fully charged.